Digital Distraction in University Students: A Critical Analysis for Higher Education Instructional Design - Harun Muhamed; Ihwana Noor Syuhada; Rahaimah Noor; Fatqurhohman Fatqurhohman (Ihsan Cahaya Pustaka, 2026)
Digital technologies have transformed higher education learning environments, providing unprecedented access to information, communication tools, and online platforms. However, this transformation has introduced digital distractions, including off-task device use, habitual multitasking, and social media engagement, which can fragment attention and reduce learning effectiveness. This study critically analyzes the phenomenon of digital distraction among university students and its implications for instructional design. Through a synthesis of empirical and conceptual studies, digital distraction is shown to be multidimensional, arising from the interaction of learner characteristics, technology features, and learning environment factors. Evidence indicates that distraction can undermine engagement, perceived learning, and satisfaction, while self-regulation and attention management strategies can mitigate these effects. Instructional design that anticipates distraction, fosters structured interaction, and ensures equitable access to learning tools is essential for optimizing student focus and outcomes. Beyond immediate classroom strategies, the findings highlight the importance of ongoing reflection on how digital environments shape attention, engagement, and educational quality. Future research should explore adaptive pedagogical approaches, technology-supported scaffolds, and systemic interventions to sustain attention and enhance learning experiences in increasingly digital and hybrid higher education contexts.